Ireland : Fifth Review Under the Extended Arrangement: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The staff report for Ireland's fifth review under the Extended Arrangement states that financial sector reforms continued to advance, with the two structural benchmarks for end-2011 observed. In particular, targets for bank deleveraging in 2011 were met, with almost Euro 15 billion of predominantly foreign assets sold at better prices than anticipated. Structural reforms have continued to progress, including the publication of reforms of the sectoral wage setting framework, and the development of a strategy for personal insolvency reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet